(untitled) (Research, Society and Development, 2023)
The article in question aims to investigate epidemiological data related to cases of exogenous intoxication by drugs resulting from self-medication in the state of Piauí (2011 to 2022). The article has a quantitative and descriptive transversal character. For data extraction, the DATASUS platform was used, using the variables: year of notification, sex, age group, schooling and city of notification. Data were organized and analyzed using graphs and descriptive statistics. 388 cases of self-medication poisoning were detected; and, through this total, it was verified that 67.53% were female, 42.27% were between 20-39 years old, 8.25% had Completed High School and 14.18% were notified in the year 2018, being the capital Teresina (28.31%) and the city of Pedro II (28.04%) with the highest percentages of registered notifications. The identification of epidemiological characteristics of the studied population indicated essential aspects for improving public health approaches. Thus, it was found that, for the cases evaluated, the prevalence was of females, aged between 20-39 years, who had completed high school.